2023
DOI: 10.1021/acssuschemeng.2c06953
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D Hierarchically Porous Chitosan Monoliths by Thermally Induced Phase Separation of Chemically Modified Chitin

Abstract: Chitosan (CS), an amino-polysaccharide, has applications in various areas such as drug delivery, biotechnology, food technology, and numerous industrial applications. Monoliths have been developed continuously for several decades, and today, they hold an impressively strong position in highly efficient separation, ion exchange, catalysis, and chromatography. In our previous study, a hierarchical chitin (CT) monolith was fabricated using chemically modified CT through the thermally induced phase separation (TIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…CS monoliths were fabricated using a thermally induced phase-separation method, as described in our previous study. , The monoliths were fabricated as follows. Five g CT powder was mixed with a solution of 95 mL of butyric anhydride and 2.2 mL of 70% perchloric acid and stirred for 3 h at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CS monoliths were fabricated using a thermally induced phase-separation method, as described in our previous study. , The monoliths were fabricated as follows. Five g CT powder was mixed with a solution of 95 mL of butyric anhydride and 2.2 mL of 70% perchloric acid and stirred for 3 h at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…This study introduces a novel and practical method for immobilizing α-amylase on a hierarchically porous CS monolith. Expanding upon previous research on the fabrication of CS monoliths using chemically modified CT and thermally induced phase separation, 36 we optimized the morphology of the monolith to achieve optimum α-amylase activity. The immobilization technique integrates physical adsorption and covalent bonding to enhance the stability of α-amylase at different pH levels and temperatures compared to its soluble form.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chitosan is an alkaline natural polysaccharide substance; in particular, it is a large molecular viscous polysaccharide formed by the partial deacetylation of chitin [ 115 ]. The amino groups on the chitosan molecular chain are easily protonated and carry a positive charge, endowing chitosan with a wide range of antibacterial properties and hemostatic effects [ 116 ].…”
Section: Nanofiber Scaffold Technologymentioning
confidence: 99%
“…Very recently, Hajili et al reported a hierarchically porous chitosan monolith fabricated via a thermally induced phase separation approach, resulting in a porous structure with a total surface area of 144 m 2 g −1 . 52 In the recent past, the use of suitable crosslinkers and changing the crosslinking density has evolved as an established mechanism to develop porous polymers, but such a process has never been well explored in the context of chitosan. Here, we use PEG diacrylate as a macro crosslinker, which is hydrophilic and soluble in water, thereby allowing us to prepare materials with wide-ranging crosslinking densities.…”
Section: Introductionmentioning
confidence: 99%